Terrorism, youth, ideals and paranoia - Bilheran, Ariane (Soins; la revue de référence infirmière, 2017)
Adolescence is a period of initiation during which individuals learn to free themselves from the hold of their impulses. Fanaticism prevents this process: the subject regresses into a paranoid-type sectarian and murderous way of functioning. The fanaticism of the adolescent could thereby be related to a distorted spiritual search for his or her purpose.